2022
DOI: 10.1142/s2424835522500102
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Outcomes of ‘Extensor Carpi Ulnaris Tenodesis’ versus ‘No Tenodesis’ after Resection of the Distal Ulna in Patients with Giant Cell Tumor

Abstract: Background: One of the methods of stabilizing the stump of the ulna following resection of the distal ulna is tenodesis of the extensor carpi ulnaris (ECU). Some studies have recommended stabilization, whereas others have not found it useful. Most of these studies have a mix of different pathologies and often do not have a control group. The aim of this study is to compare the outcomes of ECU tenodesis versus no tenodesis after resection of the distal ulna in patients with grade III giant cell tumor (GCT) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In our series, the mean QuickDASH scores of patients for the different surgery types revealed no significant disability or slight disability compared with the general population. Similar results of favorable functional scores were found in the studies of Sahito et al [ 15 ] and Papanastassiou et al [ 36 ] In the Sahito et al [ 15 ] study, no significant differences in long-term outcomes were noted between patients that received ECU tenodesis versus those without tenodesis (MWS, 91 vs 89; MSTS, 29 vs 29.2). This result was similar to that of the Papanastassiou et al [ 36 ] study in which no obvious disparity in functional outcomes were revealed using QuickDASH or MSTS.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our series, the mean QuickDASH scores of patients for the different surgery types revealed no significant disability or slight disability compared with the general population. Similar results of favorable functional scores were found in the studies of Sahito et al [ 15 ] and Papanastassiou et al [ 36 ] In the Sahito et al [ 15 ] study, no significant differences in long-term outcomes were noted between patients that received ECU tenodesis versus those without tenodesis (MWS, 91 vs 89; MSTS, 29 vs 29.2). This result was similar to that of the Papanastassiou et al [ 36 ] study in which no obvious disparity in functional outcomes were revealed using QuickDASH or MSTS.…”
Section: Discussionsupporting
confidence: 85%
“…However, it is controversial whether any type of reconstruction is needed. Most previous studies employing reconstructions were limited to cases with heterogeneous tumors and case series with small sample sizes [ 8 , 15 ]. These considerations prompted us to conduct a multicenter retrospective cohort study comprising the largest series of patients to date with GCTB of the distal ulna.…”
Section: Introductionmentioning
confidence: 99%